2003
DOI: 10.4102/sajip.v29i1.86
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among South African aircraft pilots

Abstract: In aviation, safety is paramount. The human factor is widely recognised to be critical to aviation safety and effectiveness. Numerous studies have indicated that the human factor is absolutely vital in maintaining or improving safety. These realities suggest that there is a need for consistent, long-term support for research, development, analysis and application of information related to human performance throughout the aviation system .Because this need was recognised, a United States National Plan for Aviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Ayub and Rafif concluded their study by saying that when managers basic and higher order needs are fulfilled at work, they will have positive attitude towards job and that will eventually lead to job satisfaction. In a similar vein, Hoole and Vermeulen (2003) found that the extent to which people are motivated by outward signs of position and status is positively related to their experience of job satisfaction. Another study by Megginson et al (1982) revealed that people experience job satisfaction when they feel good about their jobs, and that this feeling often relates to they doing their jobs well, or they being recognized for their good performance.…”
Section: Job Satisfaction Work Motivation and Organisational Commitmentmentioning
confidence: 63%
See 1 more Smart Citation
“…Ayub and Rafif concluded their study by saying that when managers basic and higher order needs are fulfilled at work, they will have positive attitude towards job and that will eventually lead to job satisfaction. In a similar vein, Hoole and Vermeulen (2003) found that the extent to which people are motivated by outward signs of position and status is positively related to their experience of job satisfaction. Another study by Megginson et al (1982) revealed that people experience job satisfaction when they feel good about their jobs, and that this feeling often relates to they doing their jobs well, or they being recognized for their good performance.…”
Section: Job Satisfaction Work Motivation and Organisational Commitmentmentioning
confidence: 63%
“…In line with this, Watson (1994) posits that businesses of today have realized that only a motivated and satisfied workforce can deliver powerfully to the end, even when the dike is raised. The relationship between job satisfaction and work motivation has been reported by several researchers (Megginson et al, 1982;Vinokur et al, 1994;Brown and Shepherd, 1997;Hoole and Vermeulen, 2003;Ayub and Rafif, 2011). Nevertheless, the relationship seems to be unequivocal and consistent among the several studies that have been conducted in the area.…”
Section: Job Satisfaction Work Motivation and Organisational Commitmentmentioning
confidence: 96%
“…These results are explained by the contribution that achievement makes towards a person's self-esteem (Beach, 1980), which reinforces his or her sense of contributing towards an organisation. A need for achievement is often linked to a need for power in the workplace (McClelland, 1987) and it has been shown that power is a significant predictor of job satisfaction for those workers who are motivated by it (Becherer, Morgan & Richard, 1982;Coster, 1992;Hoole & Vermeulen, 2003).…”
Section: The Relationship Among Motivation Job Satisfaction and Corpmentioning
confidence: 99%
“…Job security refers specifically to one's expectations about continuity in a job situation and extends to concern over loss of desirable job features, such as promotion opportunities and working conditions (Davy, Kinicki & Scheck, 1997). This variable has been shown to be an important predictor of job satisfaction (CohenRosenthal & Cairnes, 1991;Davy et al, 1997;Hoole & Vermeulen, 2003;Moon, 2000;Ritter & Anker, 2002;Visser, Breed & Van Breda, 1997). Studies have also shown that many employees experience job satisfaction because their affiliation needs are being satisfied to some extent at work (Cohen-Rosenthal & Cairnes, 1991;Hoole & Vermeulen, 2003;Strydom & Meyer, 2002;Van Vuuren, 1990;Visser et al, 1997).…”
Section: The Relationship Among Motivation Job Satisfaction and Corpmentioning
confidence: 99%
“…Prolific research in the area of job satisfaction has been conducted over the past few decades (Boshoff, Cilliers & Van Wyk, 2003;Buitendach & De Witte, 2005;Calder, 2000;Derlin & Schneider, 1994;Dolliver, 2003;Hoole & Vermeulen, 2003;Kh Metle, 2005;Malherbe & Pearse, 2003). However, a paucity of studies exist in the public health industry investigating job satisfaction across different occupational classes.…”
Section: Job Satisfaction In the Working Environmentmentioning
confidence: 99%